SOCIOECONOMIC CHARACTERISTICS OF CADETS OF THE MILITARY ACADEMY - vi,; Živković, Draško (The Policy of National Security, 2025)
The subject of this paper is the study of the socioeconomic characteristics of cadets at the Military Academy, attempting to define these characteristics at the individual, family, and regional levels. The aim was to gain insight into cadets' fundamental socioeconomic characteristics, descriptions, and connections to the broader socioeconomic context. Both primary and secondary data were collected for this analysis. Correlation, factor analysis, and clustering were employed. The findings indicate that regional affiliation is a crucial characteristic that can classify respondents into two groups: those from developed regions in northern Serbia and those from less developed southern regions. Additionally, the participation of female cadets is comparable to levels seen in developed European countries. Almost 70 percent of cadets come from urban and semi-urban areas, while two-fifths originate from a single region, specifically Sumadija and Western Serbia. More than half of the cadets come from working-class backgrounds, and slightly more than one-fifth have a military background. Furthermore, nearly three-quarters of cadets have completed their secondary education at a Military Grammar School or a civilian gymnasium, and the academic success achieved by over half of the cadets can be characterized as very good.
Keywords: socioeconomic characteristics; socioeconomic status; cadets; Military Academy; Serbia